2017
DOI: 10.18632/oncotarget.23080
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 (CD274) and PD-L2 (PDCD1LG2) promoter methylation is associated with HPV infection and transcriptional repression in head and neck squamous cell carcinomas

Abstract: BackgroundDNA methylation of the immune checkpoint gene PD-L1 has recently been shown to be associated with PD-L1 mRNA expression in various malignancies. This study aimed to investigate the association of PD-L1 and PD-L2 methylation with mRNA expression, immune cell infitration, protein expression and human papilloma virus (HPV) infection in head and neck squamous cell carcinoma (HNSCC) patients.ResultsDNA methylation of PD-L1 and PD-L2 correlates inversely with mRNA expression (PD-L1: p ≤ 0.002; PD-L2: p ≤ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 31 publications
3
40
0
1
Order By: Relevance
“…sPD-1 has been reported to reduce IFN-γ-mediated immunosuppression. 36 In our study we found that the level of IFN-γ was increased in miR-34a/CLMBs group and sPD-1/CLMBs group, especially in simultaneous injection of miR-34a/CLMBs and sPD-1/CLMBs groups.…”
Section: Discussionsupporting
confidence: 49%
“…sPD-1 has been reported to reduce IFN-γ-mediated immunosuppression. 36 In our study we found that the level of IFN-γ was increased in miR-34a/CLMBs group and sPD-1/CLMBs group, especially in simultaneous injection of miR-34a/CLMBs and sPD-1/CLMBs groups.…”
Section: Discussionsupporting
confidence: 49%
“…Elucidating the regulatory machinery of immune checkpoints might help to improve patient's treatment, particularly in the view of emerging immunotherapeutic strategies. Recently, inverse correlations between immune checkpoint mRNA levels and promoter methylation indicative of an epigenetic regulation as well as significant associations of immune checkpoint methylation levels with survival have been reported for several hematopoietic and solid neoplasms including acute myeloid leukemia (AML), prostate cancer, colorectal adenocarcinomas, and head and neck squamous cell carcinomas (HNSCC) ( Franzen et al, 2018 , Gevensleben et al, 2016 , Goltz et al, 2016a , Goltz et al, 2016b , Goltz et al, 2017a , Goltz et al, 2017b ). However, epigenetic association studies regarding tumors of the central nervous system are lacking so far.…”
Section: Introductionmentioning
confidence: 99%
“…Viral infections do not always enhance PD-L1 expression, because similar PD-L1 levels are detected in individuals not infected with viruses [61][62][63][64]. Increased PD-L1 levels are related to specific viruses, such as the following: Epstein-Barr virus (EBV) [65][66][67][68], hepatitis B virus (HBV) [69][70][71], hepatitis C virus (HCV) [72][73][74][75], human immunodeficiency virus (HIV) [63,[76][77][78][79], human papilloma virus (HPV) [68,[80][81][82][83], Merkel cell polyomavirus (MCPyV) [84], bovine leukemia virus (BLV) [85], and Kaposi sarcoma-associated herpes virus (KSHV) [86].…”
Section: Patients With Infectious Diseasesmentioning
confidence: 99%